1999
DOI: 10.2118/55055-pa
|View full text |Cite
|
Sign up to set email alerts
|

New Formulations of Potassium Acetate and Potassium Formate Polymer Muds Greatly Improved Drilling and Waste Disposal Operations in South Italy

Abstract: Summary This paper discusses the field results of innovative K-Acetate or K-Formate mud formulations that have been used by ENI S.p.A./Agip Division to drill several wells through very plastic shales in South Italy. Field muds have been carefully designed and evaluated as far as drilling and waste disposal activities are concerned. While drilling, the integration between field observations, standard laboratory tests, and nonconventional rheological approaches provided the assessment of useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Gillenwater and Ray (1989) documented the use of KAC in 30 wells in the South Texas area as an alternative to potassium chloride fluids and referenced that the amount of potassium provided by KAC to be 40% by weight. Gallino et al (1997) document the use of KAC for drilling plastic shales on five wells in South Italy instead of KCl. They concluded that the use of an inhibitive KAC base fluid was more environmentally acceptable than a KCl inhibitive one and resulted in lower disposal costs of per unit ton of waste produced and a large reduction of waste generated as compared to noninhibitive fluids.…”
Section: Potassium Acetate Fluidsmentioning
confidence: 99%
“…Gillenwater and Ray (1989) documented the use of KAC in 30 wells in the South Texas area as an alternative to potassium chloride fluids and referenced that the amount of potassium provided by KAC to be 40% by weight. Gallino et al (1997) document the use of KAC for drilling plastic shales on five wells in South Italy instead of KCl. They concluded that the use of an inhibitive KAC base fluid was more environmentally acceptable than a KCl inhibitive one and resulted in lower disposal costs of per unit ton of waste produced and a large reduction of waste generated as compared to noninhibitive fluids.…”
Section: Potassium Acetate Fluidsmentioning
confidence: 99%
“…The details of this unique rheological approach have been extensively discussed in previous papers 12, 13 and will not reconsidered here. When necessary, brief comments about specific tests procedures and meanings will be given during the data discussion.…”
Section: Experimental Investigationmentioning
confidence: 99%
“…Mud rings, plugged flowlines, low penetration rates, bit balling and hole instability have all been experienced. Escalating disposal costs led to the trial of a variety of chloride free mud systems and included the use of potassium acetate or potassium formate in concentrations of 25 to 30 kg/m 3 with various polymers 10,11 . Even with these formulations the muds became contaminated with fine clay solids and had threshold limits for the methylene blue test of 65 kg/m 3 above which rheology significantly increased.…”
Section: Introductionmentioning
confidence: 99%